A General Look Over Ismail Hakki Bursevi and the Period That He Lived - Öztürk, Ahmet Gökhan (Scholarya Demo Journal of Ruby, 2020)
Ismail Hakki Bursevi is a sheihk of Celvetiye sect, a poet and author who gave works on religious subjects. He had lived between 1653 and 1725. This study focuses on the relationship between the life and work of Ismail Hakki and the period that he had lived. This study is in scanning model. The information is taken from historical researches and works written about Ismail Hakki. Ismail Hakki’s works in literature and religion fields have been the subject of various research studies. This study however will covered-within the period Ismail Hakki lived. Ismail Hakki actually is from Istanbul, but since he worked in Bursa for a long time, He was known as Bursevi. He received lessons from Osman Fazli Efendi, and learned the methodology of the Celvetian sect. After the death of Osman Fazli, he undertook and held the post of sheikh of the Celvetian sects. The period when Ismail Hakki lived was when the Ottoman Turkish State had entered to a period of stagnation and the beginning of decline. The confusion in this period of time has affected both society and religious institutions. Deterioration started in the madrasahs where education and training activities were carried out and dervish lodges used by the sects for spiritual development and progress. Various schools of thought had intellectual conflicts on issues that did not concern the general public. Ismail Hakki was found in places where there were many scholars and scientists in Istanbul and Bursa. It is stated in sources that his works are over one hundred and twenty. He emphasized the development of religious institutions and the informing of the society during the stagnation and decline period.